Activities for Humanizing Dance Pedagogy: Immersive Learning in Practice. Issue 2 (3rd April 2021) - Risner, Doug
ABSTRACT: Based upon Paulo Freire's theory of humanizing pedagogy and informed more recently by Freirean scholars Lilia Bartolomé and Maria del Carmen Salazar, this practice-based article provides two immersive learning experiences in which learners engage and question their educational histories, beliefs, and values, reflecting upon and unpacking their assumptions, connecting emergent ideas to their own and others, and considering how their teaching can evolve throughout the career span. Theoretical and practical applications for dance educators and those who prepare them are offered.